LITERASI DIGITAL DALAM PENGGUNAAN SISTEM INFORMASI PENGENDALIAN TAGIHAN - Ladyta, Intan; Handayani, Yosi; Puspita, Roza (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2018)
Badan Pengawasan Keuangan Kepuluan Riau Representative is one of the government institutions which get considerable attention in its financial management. All the money used should be made accountable. Responsibility of each work unit is made using SINTAG application where the result of this input will be compiled into a document of accountability. It would be an update for the treasurer to prepare financial statements. There is a problem especially in the public relation section and administration chief representative in the input process, there is an error in inputting data such as and error in typing or nominal numbers. Such errors would generate not accurate and relevant information for expenditure treasurer in which the inputting results will be material information in financial reporting. Based on the results of the study during an apprenticeship at the Supreme Audit Board of Kepuluan Riau Representative Office, it was found that, digital literacy in using system is one of the main concern, the financial sub-section controls this issue by cross-checking the invoice with the result of input to the SINTAG application in the form of a bill control and pay order.